IMPACTS OF THE DOHA ROUND ON KOREA'S AGRICULTURAL TARIFF PROFILE - 임송수 (고려대학교, 2008)
The purpose of this paper is to simulate the proposed modality in market access and estimate its potential impacts on Korea's tariff profile. By accommodating a tiered formula for tariff reduction, the modality attempts to harmonize tariffs across products and countries. When no flexibility in tariff cuts is taken into account, Korea would face up to 68 percent reduction in tariffs in an average term (the baseline). The provision of sensitive products in which the tariff cuts are allowed to deviate from the tiered formula by two-thirds at a maximum is likely to bring about 11 percentage points of maximum tariff saving effects compared with the baseline case. Besides, Korea would be able to maximize savings in tariff reductions by 25 percentage points by designating special products. It is therefore crucial for the country to secure the right to use the provision of special products as a developing member country. Finally, it is shown that tariff cuts for tropical products would be a stiff challenge since they include many important products including rice, red pepper, Korean citrus and sesame oil.
Keywords: tariff; tiered formula; modality; market access; Doha Round; Korea; tariff; tiered formula; modality; market access; Doha Round; Korea